2022
DOI: 10.1021/acs.jafc.2c02696
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioactive Peptides from Sea Cucumber and Its Potential Health Benefits: A Comprehensive Review

Abstract: Bioactive peptides from food have been widely studied due to their potential applications as functional foods and pharmaceuticals. Sea cucumber, a traditional tonic food, is characterized by high protein and low fat, thereby substrates are being studied to release sea cucumber peptides (SCPs). Although recent studies have shown that SCPs have various bioactive functions, there is no literature reviewing the development status of SCPs. In this review, we summarized the production of SCPs, including their purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 100 publications
(247 reference statements)
1
25
0
Order By: Relevance
“…Past studies have demonstrated that the immunomodulatory ability of peptides depends on their amino acid composition, sequence, length, charge, hydrophobicity and structure [ 1 ]. The amino acids in sea cucumber are rich, including all types of essential amino acids and non−essential amino acids, and have a high content of amino acids such as glycine, glutamic acid, proline, and alanine [ 22 ]. Similarly, the amino acid composition analysis of SCH in this study revealed a high content of glycine, glutamic acid, alanine, and proline.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have demonstrated that the immunomodulatory ability of peptides depends on their amino acid composition, sequence, length, charge, hydrophobicity and structure [ 1 ]. The amino acids in sea cucumber are rich, including all types of essential amino acids and non−essential amino acids, and have a high content of amino acids such as glycine, glutamic acid, proline, and alanine [ 22 ]. Similarly, the amino acid composition analysis of SCH in this study revealed a high content of glycine, glutamic acid, alanine, and proline.…”
Section: Discussionmentioning
confidence: 99%
“…The capillary isoelectric focusing electrophoresis separates analytes based on their different isoelectric points. It is generally used to separate peptide isomers [ 65 , 66 , 67 ].…”
Section: Production Methods For Natural Biopeptidesmentioning
confidence: 99%
“…Furthermore, these peptides enhance the expression of LPL and CPT1 , which are key rate-limiting enzyme genes for lipoprotein hydrolysis and FA β-oxidation, respectively ( Yu et al, 2020 ). The peptides isolated from sea cucumber Stichopus japonicas can increase the content of unsaturated lipids in mouse and rat hippocampus ( Lu et al, 2022a ). As unsaturated lipids can modulate lipid metabolism ( Djuricic and Calder, 2021 ; Mitrovic et al, 2022 ), the above results suggest that peptides alleviate hyperlipidemia by regulating the metabolism of unsaturated lipids.…”
Section: The Lipid-modulatory Mechanisms Of Sea Cucumber-derived Comp...mentioning
confidence: 99%
“…The saponins from Holothuria lessoni contribute to the anti-oxidant activity of this sea cucumber extracts ( Bahrami et al, 2018 ). The health-beneficial effects including antioxidant, anti-diabetes, and immunomodulatory activities of sea cucumber peptides have been recently reviewed ( Lu et al, 2022a ).…”
Section: The Sea Cucumber-devived Coumpounds For Treatment Of Cardiac...mentioning
confidence: 99%